Cultural Aspects of Suicide - Hari D. Maharajh; Petal S. Abdool (The Scientific World Journal)
Undefined cultural factors cannot be dismissed and significantly contribute to the worldwide incidence of death by suicide. Culture is an all embracing term and defines the relationship of an individual to his environment. This study seeks to investigate the effect of culture on suicide both regionally and internationally. Culture-bound syndrome with suicidal behaviours specific to a particular culture or geographical region are discussed. Opinions are divided as to the status of religious martyrs. The law itself is silent on many aspects of suicidal behaviour and despite decriminalization of suicide as self-murder, the latter remains on the statutes of many developing countries. The Caribbean region is of concern due to its steady rise in mean suicide rate, especially in Trinidad and Tobago where socio-cultural factors are instrumental in influencing suicidal behaviour. These include transgenerational cultural conflicts, psycho-social problems, media exposure, unemployment, social distress, religion and family structure. The methods used are attributed to accessibility and lethality. Ingestion of poisonous substances is most popular followed by hanging. The gender differences seen with regard to suicidality can also be attributed to gender related psychopathology and psychosocial differences in help-seeking behaviour. These are influenced by the cultural environment to which the individual is exposed. Culture provides coping strategies to individuals; as civilization advances many of these coping mechanisms are lost unclothing the genetic predisposition of vulnerable groups. In the management of suicidal behaviour, a system of therapeutic re-culturation is needed with an emphasis on relevant culture- based therapies.